Phyag chen ihan cig skyes sbyor dṅos gźiʼi khrid yig cuṅ zad spros pa sems kyi rdo rjeʼi ṅes gnas gsal bar byed pa - ʼJam-dpal-dpaʼ-bo, Bde-chen-chos-ʼkhor Yoṅs-ʼdzin IV, 1720-1780 (1969)
Explanatory induction of the praxis of Mahamudra focussing on the union of the tutelaries, Chakrasamvara and Varahi, according to the Cakrasamvara Tantra.